2022
DOI: 10.3390/ejihpe12120132
|View full text |Cite
|
Sign up to set email alerts
|

Digital Pandemic Stress in Higher Education in Venezuela

Abstract: The COVID-19 pandemic had a great impact on the process of integrating digital technologies in higher education and caused digital stress among professors, mainly in countries with a lower level of digitalization. In this work, quantitative research was carried out on the stress of professors in Venezuela due to the digitalization of their teaching activities caused by the pandemic, and gender gaps were identified in this regard. This digital stress was compared with that of professors in other countries with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 79 publications
2
4
0
Order By: Relevance
“…It is also found that female professors both in private and public universities manifest slightly higher levels of pandemic digital stress than male professors, with no significant difference in the behavior of this gender gap by university tenure ( Table 5 ). This is consistent with the results obtained by previous work in the specific setting of Venezuela, but not with the results obtained in countries with low levels of digitization in Latin America, such as Guatemala, Honduras, and Bolivia [ 51 ]. Therefore, the results suggest that there is a strong variability between countries with respect to the behavior of gender gaps in private and public universities, which offers the results presented here as an average.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is also found that female professors both in private and public universities manifest slightly higher levels of pandemic digital stress than male professors, with no significant difference in the behavior of this gender gap by university tenure ( Table 5 ). This is consistent with the results obtained by previous work in the specific setting of Venezuela, but not with the results obtained in countries with low levels of digitization in Latin America, such as Guatemala, Honduras, and Bolivia [ 51 ]. Therefore, the results suggest that there is a strong variability between countries with respect to the behavior of gender gaps in private and public universities, which offers the results presented here as an average.…”
Section: Discussionsupporting
confidence: 91%
“…However, it has been observed that the variability of Latin American and Caribbean professors’ responses in terms of pandemic digital stress levels is high compared to the other response families (1.25 out of 5), indicating that there is much divergence among professors’ stress levels. This strong variability is consistent with the results of other work on pandemic digital stress carried out on samples of professors from more restricted geographical areas such as Venezuela [ 51 ]. The originality and novelty of the present work lies in the finding that strong unevenness of pandemic digital stress is found throughout the Latin American and Caribbean region.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Daily stress has a more significant negative effect on career confidence. Studies suggested that chronic stress can lead to burnout, which can lower career confidence, and even lead to quitting in turn [ 71 ]. Therefore, Compas [ 72 ] concluded that both primary, and secondary controlled participation coping are associated with adaptive mental health, including enhancement of positive emotions, and reduction of negative emotions, and effective coping occurs when the positive effects of coping or protective factors outweigh the negative effects of stressors [ 73 ], thus improved adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing job demands especially in digital work contribute to increasing work-related stress, 7 , 8 but can also have positive effects. 8 In addition, work-family conflict due to remote work can increase stress.…”
Section: Introductionmentioning
confidence: 99%